GENDER EQUALITY IN EDUCATIONAL LITERACY IN LANGSA - sarah ziehan harahap; Chairuddin Chairuddin; Evi Zulida; Makhroji Makhroji; fadlia Fadlia (Universitas Samudra, 2019)
This research offers and overview of the main developments in the field of Sociolinguistic studies. The education should be equal in both gender, no matter the background is. This paper examine the characteristics and the factors of inhibiting the gender equality in educational literacy in Langsa. The purpose of this research are: to find out how are the characteristics of gender equality in educational literacy in Langsa and to find out what are the factors that could inhibit gender equality in educational literacy. This research uses descriptive qualitative methods, namely observation, semi-structured interviews, and documentation. The subjects of this research are twenty parents (ten men and ten women) in Langsa. The research instruments were questions, recording equipment and documentation. The procedure for collecting data is library research, conducting interviews, voice recorders and concluding. The results of this research are the characteristics of gender equality in educational literacy and the factors could inhibit the gender equality in educational literacy in Langsa. Key words: Gender, Equality, Inequality, Education, Langsa